Flexible high aspect ratio wing: Low cost experimental model and computational framework - Pontillo, Alessandro; Hayes, David; Dussart, Gaétan X.; Lopez Matos, Guillermo E.; Carrizales, Martin A.; Yusuf, Sezsy Y.; Lone, Mohammad M. (AIAA, 2018)
Aircraft concepts of tomorrow, such as high aspect ratio wing aircraft, are far more integrated between technical disciplines and thus require multidisciplinary design approaches. Design tools able to predict associated dynamics need to be developed if such wing concepts are to be matured for use on future transport aircraft. The Cranfield University Beam Reduction and Dynamic Scaling ( BeaRDS) Programme provides a framework that scales a conceptual full size aircraft to a cantilevered wing model of wind tunnel dimensions, such that there is similitude between the static and dynamic behaviour of the model and the full size aircraft. This process of aeroelastically scaled testing combines the technical disciplines of aerodynamics, flight mechanics and structural dynamics, to provide a means by which future concept aircraft can be de-risked and explored . Data acquisition from wind tunnel testing can then be used to validate fluid-structure interaction frameworks that model the aeroelastic effect on the flight dynamics of the aircraft. This paper provides an overview of the BeaRDS methodology, and focuses on the Phase I of the programme, being the development of a reduced Cranfield A-13 aircraft cantilevered wing, to mitigate risk associated with the manufacturing and instrumentation app roach. It is shown that a low cost acquisition system of commercial Inertial Measurement Units (IMUs) can measure the response of the wing within the desired frequency range. Issues associated with the Phase I testing are discussed, and methods are proposed for the Phase II programme that allow these problems to be resolved for a larger scale flexible wing with active control surfaces.